Rust Conversion Studies Of Archeological Irons From Fort Cornwallis Using Modified Oil Palm Fronds Lignin - Osman, Liyana Syafawati (2024)
This research reveals the structural and antioxidant properties of extracted organosolv lignin samples derived from oil palm fronds (OPF) pretreated with autohydrolysis upon incorporation with 1,5-dihydroxy naphthalene (AHD EOL) and p-benzoquinone (AHPB EOL) and steam explosion pretreatment impregnated with diluted sulfuric acid (SEA EOL). It was revealed that AHPB EOL had the highest percentage of yield among other organosolv lignin samples (% yield AHPB EOL: 13.79 ± 0.17% > % yield SEA EOL: 13.66 ± 0.35% > % yield AHD EOL: 13.09 ± 1.03% > % yield AH EOL: 12.40 ± 1.18%). Various organosolv lignin samples were then evaluated with elemental analysis, Fourier transform infrared (FTIR), nuclear magnetic resonance (NMR), gel permeation chromatography (GPC), thermogravimetric (TGA), differential-scanning calorimeter (DSC), solubility test, and antioxidant activity. Throughout the analyses, modified organosolv lignin (AHD EOL and AHPB EOL) and steam explosion acid impregnation organosolv lignin (SEA EOL) exhibited smaller lignin matrix with higher phenolic content (phenolic-OH SEA EOL: 0.60/Ar > phenolic-OH AHPB EOL: 0.47/Ar > phenolic-OH AHD EOL: 0.45/Ar > phenolic-OH AH EOL: 0.40/Ar), which leads to higher water solubility (D% SEA EOL: 29.50 ± 0.11% > D% AHPB EOL: 24.25 ± 0.13% > D% AHD EOL: 22.50 ± 0.16% > D% AH EOL: 20.50 ± 0.22%) and antioxidant activity compared to unmodified organosolv lignin (AH EOL).